Antimicrobial and SEM studies of sophorolipids synthesized using lauryl alcohol - Dengle-Pulate, Vrushali; Chandorkar, Parul; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2014)
In recent years, researchers have developed biosurfactants for industrial, pharmaceutical and medical applications revealing the promising biological activities of these biomolecules. One of the best studied microbial surfactants are glycolipids, especially sophorolipids (SLs) produced by selected non-pathogenic yeast species of Candida. They are biodegradable, non-toxic and are environmentally friendly. Sophorolipid production was carried out using glucose as the hydrophilic source and lauryl alcohol C12-14, as the hydrophobic source using Candida bombicola ATCC 22214. Primary characterization of the SL obtained using lauryl alcohol (SLLA) was done by FTIR which depicted the presence of alkyl sophorosides/SLs. Antimicrobial activity testing revealed that SLLA showed complete inhibition against gram negative bacteria, Escherichia coli (ATCC 8739) Pseudomonas aeruginosa (ATCC 9027) at 30 and 1 mu g/ml at a contact time of 2 and 4 h respectively. Whereas for gram positive bacteria Staphylococcus aureus (ATCC 6358), Bacillus subtilis (ATCC 6633), complete inhibition was observed at 6 and 1 mu g/ml respectively at a contact time of 4 h. The formed SLLA showed noteworthy inhibition against the pathogenic yeast Candida albicans (ATCC 2091) at 50 mu g/ml with a contact time of 4 h. These values are remarkably low compared to reported values of oleic acid SLs and linolenic acid SLs which were studied for antimicrobial properties. Scanning electron microscopy analysis of the treated cells revealed the changes in morphology and topography of the microorganisms.
Keywords: Antimicrobial property; Biosurfactants; Candida bombicola; Lauryl alcohol; sophorolipids